2015
DOI: 10.1007/s00125-015-3561-4
|View full text |Cite
|
Sign up to set email alerts
|

Forkhead box O1 mediates defects in palmitate-induced insulin granule exocytosis by downregulation of calcium/calmodulin-dependent serine protein kinase expression in INS-1 cells

Abstract: Aims/hypothesis The transcription factor forkhead box O1 (FOXO1) induces pancreatic islet beta cell endoplasmic reticulum stress and is involved in fatty-acid-induced insulinsecretion defects. Cask is a downstream target gene of FOXO1. Using INS-1 cells with palmitate-induced insulinrelease defects, we investigated the relationship between FOXO1 and Cask. Methods The expression levels and location of calcium/ calmodulin-dependent serine protein kinase (CASK) and FOXO1 were evaluated by real-time PCR, western b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 35 publications
2
19
0
Order By: Relevance
“…In our future studies, we will aim at identifying the mechanisms underlying this difference. Previous studies have shown that FoxO1 inhibits insulin granule exocytosis through downregulation of Cask expression in INS-1 cells [45]. Our study confirmed that the Wnt5a protein can suppress the expression of pFoxO1, but the expression of Cask did not increase accordingly.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In our future studies, we will aim at identifying the mechanisms underlying this difference. Previous studies have shown that FoxO1 inhibits insulin granule exocytosis through downregulation of Cask expression in INS-1 cells [45]. Our study confirmed that the Wnt5a protein can suppress the expression of pFoxO1, but the expression of Cask did not increase accordingly.…”
Section: Discussionsupporting
confidence: 84%
“…ese experimental results are consistent with those of previous studies. Many genes are related to the insulin secretion from β-cells, for example, β-cell transcription factors (PDX1, Rfx6, and NeuroD1); insulin gene transcription factors; genes mediating GSIS, such as FoxO1, PDX1, Glut2, Gck, Abcc8, and Kcnj11; and genes mediating insulin granule exocytosis (Cask) [42][43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…CASK was of particular interest as a member of the membrane-associated guanylate kinase (MAGUK) protein family that helps initiate assembly of the presynaptic secretory machinery. CASK is involved in exocytosis of neurotransmitters in the brain (Atasoy et al 2007) and of insulin in the endocrine pancreas (Suckow et al 2008;Wang et al 2015). Furthermore, Uniprot and Interpro annotations show that exon 11 of Cask, which is skipped more frequently in the circadian mutants, encodes a domain that facilitates interactions with synaptic membrane proteins ( Fig.…”
Section: Thyroid Hormone Receptor Associated Protein 3 (Thrap3) Regulmentioning
confidence: 99%
“…In pancreatic islet beta cells, CASK knockdown reduced the anchoring of insulin vesicles to cell membranes and insulin release (Wang et al . ).…”
Section: Brief Depolarization Pulses Promote the Synchronic Release Omentioning
confidence: 97%
“…There is also data suggesting that the disruption of Mint1-Munc18-1 binding decreases secretion in chromaffin cells (Graham et al 2011). In pancreatic islet beta cells, CASK knockdown reduced the anchoring of insulin vesicles to cell membranes and insulin release (Wang et al 2015).…”
mentioning
confidence: 99%